Investigation of wireless pulse oximeters for smartphone-based remote monitoring of lung health - Melnyk, Anatoliy; Morozov, Yuriy; Havano, Bohdan; Hupalo, Petro (Lviv Politechnic Publishing House, 2020)
Coronavirus has the greatest effect on the human lungs. This is why lungs of patients with COVID 19 require constant medical monitoring. One of the tools for the lungs condition monitoring is based on the wireless pulse oximeters connected to smartphones. The re is an attempt to analyze the types of pulse oximeters, their technical characteristics, principles of operation and basic requirements for these measuring instruments in the article. According to this study, the most effective pulse oximeters for 24/7 monitoring of lung function were selected. Principles of pulse oximeter functioning and mathematical basis of its operation have been described. The criteria for pulse oximeter selection have been determined, and comparative analysis of pulse oximeters with wireless communication has been conducted.
Keywords: hypoxemia, COVID-19, pulse oximetry, oxygen saturation, mobile applications, remote patient monitoring